Chemical composition and antioxidant activity of phenolic extracts from peanut skins obtained by different industrial process - Larrauri, Mariana (2014)
Fil: Larrauri, Mariana. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.